Aktivitas Pengelolaan Media Sosial Sebagai Media Informasi Kesehatan Mental Pada Instagram @Howslife.Id - Meliana, Tiara; Abdurahman, Ade Irfan; Mirza, Mochammad (Peneliti.net, 2024)
Mental health conditions must be balanced with physical health conditions, mental disorders can cause problems in daily activities. In the organizational aspect, the use of internet technology is quite important for organizations in carrying out publication activities. This research is aimed at finding out social media management activities as a medium for mental health information on Instagram @howslife.id. Lack of knowledge and interest in mental health platforms makes Instagram users less trusting of online media such as @howslife.id. To achieve this goal, researchers use qualitative descriptive methods that describe the condition of objects systematically, accurately, factually and in detail. The collected data is processed to produce accurate data. The results obtained are activities in managing Instagram social media through scheduling and managing social media in conveying messages or information and communicating with the audience, becoming a content creator to create interesting content and providing information facilities to the audience, disseminating information about mental health and counseling programs in How's Life or @howslife.id, then increases the trust of Instagram users.